ANALYSIS AND JUSTIFICATION OF NORMATIVE SUPPORT OF EARTH DESIGN DESIGN IN COMPLEX ENGINEERING AND GEOLOGICAL CONDITIONS: Array - Batrakova, A.; Dorozhko, Y.; Zakharova, E. (Municipal economy of cities. Series: «Economy science», 2021)
Designing of a ground cloth is the most responsible stage as destruction or inadmissible deformations of a ground cloth connected with design errors lead to decrease in reliability of all constructive elements of highways, increase in expenses for maintenance of a standard technical and operational condition of road clothes, culverts, elements. arrangement, etc. Insufficient strength of the ground structure is one of the causes of deformations and destruction of the structure of the pavement, which leads to deteriorating traffic conditions, increased damage from traffic accidents, increased cost of transportation and more. At the same time, the normative documents on road design do not contain any regulations on the procedure and methods of calculating the road surface in difficult conditions (on weak, subsidence soils, in rocky soils). Therefore, in order to further develop the list of mandatory calculations during the design of the ground, it is necessary to analyze and generalize the regulatory framework for the construction of the ground of public roads, to determine the requirements for the design of the ground in complex engineering and geological conditions. The purpose of this study is to generalize the regulatory requirements for the design of the ground of public roads in complex engineering and geological conditions. According to the results of the analysis, it is established that in the normative documents on the design of the road surface in difficult engineering and geological conditions there is no regulation on the procedure and methods of calculating the road surface in difficult conditions (on weak, subsidence soils, in rocky soils). Therefore, there is a need to develop a national standard for the design of the road surface. In the future it is necessary to summarize the existing methods of calculating the road surface, to develop a list of mandatory calculations during the design of the road, to establish requirements for the principles and procedures of road construction, to determine the boundary conditions of the road and their criteria.